Phenylephrine eye drops in pediatric patients undergoing ophthalmic surgery: incidence, presentation, and management of complications during general anesthesia. Issue 4 (19th December 2013) - Sbaraglia, Fabio; Mores, Nadia; Garra, Rossella; Giuratrabocchetta, Giuseppe; Lepore, Domenico; Molle, Fernando; Savino, Gustavo; Piastra, Marco; Pulitano', Silvia; Sammartino, Maria; Lerman, Jerrold
Summary Background Phenylephrine eye drops are widely used as mydriatic agent to reach the posterior segment of the eye. In literature, many reports suggest a systemic absorption of this agent as a source of severe adverse drug reactions. Hence, we reviewed our experience with topical phenylephrine in ophthalmic surgery. Methods In May 2006, following US guidelines publication, a standard operating procedure was issued in our operating rooms to standardize the use of phenylephrine eye drops in our practice. Two years later, after the occurrence of a cluster of serious adverse drug reactions in infants undergoing surgery, a review of phenylephrine safety and systemic complications incidence was performed. Results We observed 451 pediatric patients, and 187 met the inclusions criteria: Among them, 4 experienced hemodynamic complications due to phenylephrine eye drops. The incidence of major complications was 2.1%. Conclusions Two different patterns of side effects occurred. The first one was a cardiovascular derangement with severe hypertension and heart rate alterations; the other one involved exclusively pulmonary circuit causing early edema. These clinical manifestations, their duration, and treatment responses are all explainable by alfa1‐adrenergic action of phenylephrine. This hypothetic pathogenesis has been confirmed also by the usefulness of direct vasodilators (anesthetic agents) and by the negative outcome occurred in the past with the use of beta‐blockers.